Development of fast disintegrating tablet formula of ketoprofen-β-cyclodextrin inclusion complexes - Rachmawati, Heni; Marbun, Estherina Juliana; Pamudji, Jessie S. (INDONESIAN JOURNAL OF PHARMACY, 2011)
Ketoprofen  is  one  of  non  steroidal  anti  inflammatory  drugs  (NSAID)  used for  rheumatoid  arthritis.  However,  unpleasant  taste of  ketoprofen  leads  to difficulty  in  the  formulation,  in  particular  for  oral  route.  Therefore,  in  present study, a technique to mask the unacceptable taste of ketoprofen was developed. Then,  a  fast  disintegrating  tablet  on  this  inclusion  complex  was  established  for rapid  release  and  faster  analgesic  effect  of  ketoprofen.  Taste  masking  was prepared  by  complex  inclusion  with  β-cyclodextrin.  The  ratio  of  ketoprofen  and β-cyclodextrin  was  varied.  The  fast  disintegrating  tablet  was  formulated  with direct compression using various ratios of mannitoland lactose as tablet diluent, the main factor influencing the successful of fast disintegrating tablet. Evaluation of  final  product  was  performed  according  to  compendial  standard  and  specific requirements  for  fast  disintegrating  tablet.  The  best  ratio  from  ketoprofen  and β-cyclodextrin  was  2:3  with  concentration  of  ketoprofen  in  inclusion  complex was  40.32%.  The  tablet  met  standard  requirement  was resulted  with  the composition  of  ketoprofen-cyclodextrin  equivalent  to  50  mg  of  pure  ketoprofen and mannitol and lactose (ratio 1:1) as tablet diluent. Fast disintegrating tablet of  modified  ketoprofen  in  inclusion  complex  was  fulfilled  standard  specification for ketoprofen tablet with better acceptance.Key words:ketoprofen, inclusion complex, fast disintegratingtablet, beta cyclodextrin.